LEUKEMIA SEL PLASMA - Wiwin H; DB. Hadiwidjaja (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
A woman 40 years old, with pathologic fractures confirmed by radiological examination. She has a history of chronic bone painin her leg and pelvis. Laboratory examination reveals classical data of multiple myeloma, but with increased plasma cell leukemia inperipheral blood. It is necessary to differenciate plasma cell leukemia with multiple myeloma especially in high degree proliferatingterminal stage. Recommendation for a new method ie flowcytometry immunophenotyping has been proposed for hemato-oncology.